The influence of Cabernet Sauvignon wine grape pomace powder addition on the rheological and microstructural properties of wheat dough. Issue 1 (1st January 2021) - Lou, Wenjuan; Li, Bo; Nataliya, Grevtseva
ABSTRACT: Grape seed powder (GSP), grape skin powder (GSKP), or grape pomace powder (GPP) was introduced as partial substitution for wheat flour (WF) with variable percentages by weight (0– 20 wt%), and the resultant addition effects on the rheological and microstructural properties were studied. GPP and GSP significantly ( p < .05) reduced the water absorption but three types of grape powders could increase the development time and dough stability. Furthermore, all kinds of grape powders with various incorporations could significantly ( p < .05) enhance the strength of dough systems. Grape powders decreased the storage (G′) and loss (G″) moduli, while the tan δ increased with the increasing of GSP/GSKP/GPP addition levels. The microstructure observation of composite doughs suggested that the integrity and continuity of gluten networks were destroyed in the presence of grape powders. Based on the above results, the GSP addition levels of 10% to 15%, GSKP/GPP of 5% to 10% are recommended.